Pengaruh Varian Produk terhadap Keputusan Pembelian Makanan Kekinian - Achmad Ali Yafi K; Eliya Putri Aprilia; M Najib Zakariya; Moh Riski; Nurul Agustin; Didit Darmawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This literature study examines the influence of Product Variants on Purchasing Decisions on Food products. Product Variants are one of several important aspects that manufacturers need to consider when making a product, because product variants play a role in providing a choice for consumers, product variants mean that each product produced by the company has various styles or categories. Product diversity is assessed based on two factors: product line diversity and differences in packaging size. Product line diversity indicates differences in characteristics such as brands, flavors, or ingredients. Packaging size diversity refers to differences in the amount found in a package. Having various styles or categories. Product diversity is assessed based on two factors: product line diversity and differences in packaging size. Product line diversity indicates differences in characteristics such as brands, flavors, or ingredients. Packaging size diversity refers to differences in the amount found in a package. This literature study aims to analyze and synthesize previous research findings regarding the role of product variants on purchasing decisions and identify other factors that influence product variants on food purchasing decision making. This study was conducted using a literature review method that analyzed various related sources. The results obtained from this study indicate that product variants have a positive and significant influence on food purchasing decision making.